Evaluasi Penjadwalan Pembangunan Pembangkit Listrik Terapung Dengan Menggunakan Metode Project Evaluation Review Technique (PERT) - Kawuri, Pangestika Oirala; Sumiati, Sumiati (Universitas Nahdlatul Ulama Blitar, 2025)
This research aims to optimize existing project schedule plans so that time can be used more effectively and efficiently. Through the method used, it is hoped that we can find out the sequence of methods that can provide optimal results for the needs of the production acceleration aspect in project schedule planning at PT X Indonesia. This research uses quantitative methods by processing data obtained from the company. The method that will be used in this analysis is the Project Evaluation Review Technique (PERT). After processing the data using the Project Evaluation Review Technique method, it can be seen that there are 6 critical jobs. From the calculation results obtained at Z = 3.55, the Z value on the normal distribution curve is 0.9998 so that the probability that the project can be completed in 213 days is 99.98%. This means the project can be completed 16 days faster than it should be, where initially the project could be completed in 229 days.